Assessing the Utility of an Outpatient Exercise Program for Children With Cystic Fibrosis: A Quality Improvement Project - Adair, Dionne; Hider, Ahmad; Filbrun, Amy G.; Tapley, Chris; Bouma, Sandra; Iwanicki, Courtney; Nasr, Samya Z. (Frontiers in Pediatrics, 2022)
Children with CF (cwCF) suffer from inadequate weight gain, failure to thrive & muscle weakness. The latter may be secondary to disuse atrophy (muscle wasting or reduction in muscle size associated with reduced physical activity and inflammation. Hand grip strength (HGS) is a reliable surrogate for muscle strength and lean body mass. Data from our CF center has shown an association between low HGS and FEV1 in cwCF. High Intensity Interval Training (HIIT) improves physical strength. Therefore, we devised a project to assess implementing a HIIT exercise program in the home setting, in order to improve physical strength in cwCF with HGS ≤ 50th percentile. Patients were instructed to complete 3-5 sessions of HIIT exercises per week. Wilcoxon matched-pairs signed rank tests were used to compare HGS, FEV1 & BMI percentile at baseline and at a follow up clinic visit. Follow up was limited due to the COVID pandemic. Adherence to the HIIT regimen was poor. A total of twenty nine cwCF participated in the program. However, a total of 13 individuals reported some form of moderate activity at follow up and therefore constituted our final study population. There was a statistically significant increase in Absolute Grip Strength (AGS) and FEV1 for these individuals. Even though the home HIIT protocol was not followed, the project demonstrated that moderate physical activity in cwCF can lead to significant improvement in HGS and overall physical strength.